Social Ties in a Public Good Experiment - Frans van Dijk; Joep Sonnemans; Frans van Winden (Tinbergen Institute, 1996)
The formation of social ties is examined in an experimental study of voluntary public good provision. The experiment consists of three parts. In the first part the value orientation (attitude to a generalized other) ismeasured. In the second part couples play 25 periods of a public good game. In the third part the attitudes of subjects to their partners in the public good game is measured. The concept of a social tie is operationalizedas the difference between the measurements in the first and third parts. Evidence for the occurrence of social ties is found. These ties depend on the success of the interaction in the public good game.
Keywords: C91; H41; A13; 330; Public good; social ties; experiment; Öffentliche Güter; Test; Soziologie; Theorie